Pressure injury risk assessment and prevention strategies in operating room patients – findings from a study tour of novel practices in American hospitals - Lauren Goudas; Steven Bruni (Journal of Perioperative Nursing)
Hospital-acquired pressure injuries (HAPIs) lead to complications such as increased pain, increased bed days, re-admissions, multiple surgical interventions, possible disfigurement, decreased quality of life, increased health care cost and mortality. However, HAPIs are preventable and financial penalties have been imposed in some parts of the world as a strategy for ensuring hospitals comply with standards of practice to prevent them from occurring. In the United States of America, the Centers for Medicare and Medicaid Services developed guidelines that deny reimbursement for care required due to HAPIs across hospitals in the United States of America. In the Australian context, pressure injury has been identified as a hospital-acquired complication with the potential to affect an organisation’s revenue. In Queensland, public hospitals attract significant penalties for failing to prevent pressure injuries with fines ranging from $30 000 and $50 000 for Stage 3 and Stage 4 HAPIs, respectively.